The Effect Of Gallery Walk Learning Model To Improve Students' Creativity In Elementary School Fine Arts Subjects - Nia Agis Susanti; Angga Setiawan; Indah Yunitasari (JOSAR (Journal of Students Academic Research), 2025)
Teachers play a crucial role in fostering innovative and engaging learning environments to ensure that educational goals are effectively achieved. Selecting an appropriate learning model can significantly support the development of student creativity, particularly in Fine Arts, a subject that heavily relies on imagination and personal expression. The creativity levels among fourth-grade elementary students remain relatively low, as reflected in their limited ability to generate original ideas and the lack of variety in instructional models used by teachers, which are still largely traditional and project-based. This research aims to examine the impact of the Gallery Walk learning model on enhancing student creativity in Fine Arts. A quantitative approach was employed using a Quasi-Experimental method with a Nonequivalent Control Group Design. The study population included all fourth-grade students in Pule District, totaling 578 students. From this population, 82 students were selected through purposive sampling from SD Negeri 1 Joho, SD Negeri 4 Pule, and SD Negeri 2 Joho. Data were gathered through observation, interviews, and documentation, using instruments such as creativity rating scales and product assessment tools. The results of the hypothesis test, conducted using an independent samples t-test, indicated a significance value of 0.000 ≤ 0.05, demonstrating a meaningful effect of the Gallery Walk model on improving student creativity. This model has proven effective in encouraging students to express their creative ideas more fully in Fine Arts learning.